The Changing Role of Women in Resilience, Recovery and Economic Development at the Intersection of Recurrent Disaster: A Case Study from Sirajgang, Bangladesh. (February 2017) - Islam, Mir Rabiul; Ingham, Valerie; Hicks, John; Manock, Ian
Two million people were affected in the floodplains and low-lying areas in Sirajgang in 2012. Seven hundred and fifty families were made homeless and forced to live in small temporary huts on the river protection embankments. Unemployment rose alarmingly and the jobless left their villages to find work in larger cities, leaving behind their vulnerable and insecure families. Consequently, women were increasingly required to take on totally unfamiliar roles. Our research utilised in-depth interviews with women managing without the support of their husbands. Key findings highlighted that community resilience would improve if these women were engaged at the local operational level of disaster management.